Pemanfaatan Aplikasi Canva dalam Meningkatkan Hasil Belajar Pendidikan Agama Islam Kelas IV SD Al Qur’an Wahdah Islamiyah Bontang Tahun Pelajaran 2023/2024 - Diadara, Syarifah; Utama, Putri Bagaskara (Sekolah Tinggi Ilmu Tarbiyah Syamsul Ma'arif Bontang, 2025)
Utilization of the Canva Application in Improving the Learning Outcomes of Islamic Religious Education Class IV of Al Quran Wahdah Islamiyah Elementary School, Bontang, Academic Year 2023/2024. This study aims to determine the Role of Islamic Religious Teachers in Improving the Learning Motivation of Class IV Students of Al Quran Wahdah Islamiyah Elementary School, Bontang, Academic Year 2023/2024. And to determine the increase in learning motivation of class IV students of Al Quran Wahdah Islamiyah Elementary School, Bontang, Academic Year 2023/2024. The research approach is a qualitative approach, meaning that the research uses observation, interviews, and documentation. The results of the study show that the role of Islamic religious teachers begins by motivating students about the importance of understanding Islam. In addition, Islamic religious teachers use appropriate learning methods that can support increasing student learning motivation, namely discussion and question and answer methods. Furthermore, Islamic religious teachers play games before starting learning so that there is a passion for learning that provokes students' enthusiasm for learning. Islamic cultural history teachers encourage and motivate students so that there is a passion for learning. The conclusion of this study, the Role of Islamic Religious Teachers in improving the Learning Motivation of Grade IV students of SD Al Quran Wahdah Islamiyah Bontang can be said to be successful. This can be seen from the increase in student learning motivation and also from student answers during interviews related to the benefits that students get from the role of Islamic religious teachers in improving learning motivation. These benefits include: students become more active in learning than before, habits increase motivation, students can convey ideas or opinions fluently, and improve student learning activities.